Use Of Urea Deep Placement Technology Among Rice Farmers In Kwara State, North Central Nigeria - Sola Emmanuel Komolafe; Adeseye O Awoyemi; Ridwanullahi Ridwanullahi; Gbolagade B Adesiji (Serambi Journal of Agricultural Technology, 2019)
Assessing the level farmers’ usage of fertilizer deep placement is important to improve the efficiency of soil nutrient. Extension organisations responsible for the dissemination of the technology will immensely benefit by knowing the level of usage of the technology for future extension programme implementation. In light of this, we examined the use of urea deep placement technology among rice farmers. Frequency count was used to identify rice farmers that use Urea Deep Placement technology and Pearson Product Moment Correlation (PPMC) was employed to determine factors associated to use of the technology. The study found that majority (85.8%) were aware of UDP technology between the year 2012 to 2013 (61.6%) mainly through agricultural extension agents (55%) and fellow farmers (25%). Majority (81.7%) tried it but few (11.7%) adopted it. Labour intensiveness (58.3%) is one of the reasons for non-adoption while the few adopters (10%) adopted because the technology increases productivity. Age of farmers is positively related the use of UDP technology. The study focuses on the use of urea deep placement technology provided by extension services among farmers; however, these farmers may have an interest in other types of fertilizer and methods of application that have not been investigated. The study provides an insight to show the usage of UDP among farmers engaged in rice production as a means to improve the efficiency of soil nutrient.